Being in countryside culture and art: the perspective of lithuanian philosophy - T. Kavaliauskas, (Ukrainian Cultural Studies, 2018)
The article analyses Lithuanian philosophy of Being in countryside culture and art. Lithuanian philosopher A. Šliogeris following Martin Heidegger is in ontological longing for grasping Being outside the city in a countryside and in visual art of painting that expresses Being in nature. French painter Paul Cézanne serves to him as an example of such effort. The picture of a pine tree is supposed to have more intensity of Being than the original pine tree in Provence where Cézanne painted it. If Heidegger’s example of Being in painting was Van Gogh’s pair of shoes, so Šliogeris’s example is Cézanne’s pine tree. The critique of the article is based on the argument that Heidegger and his Lithuanian follower Šliogeris were not concerned with how impressionistic concept and painting technique evolved and how it remained only one art concept out of many. Heidegger used Van Gogh’s pair of shoes and Šliogeris used Cézanne’s pine tree for the purpose of illustration of their art philosophy of Being; however, such approach neglected that these painters belong to only one school of European painting history of impressionism, therefore, it is unjust to glorify them as the only ones to be capable of expressing Being in painting.
Keywords: Being, thing, Heidegger, Šliogeris, Alpha reality, Omega reality, countryside